SMEs innovation and job creation potential in the shadow economy context - Stawasz, Edward; Głodek, Paweł (Comparative Economic Research. Central and Eastern Europe, 2011)
The presented paper treats about the ability of creating new jobs by innovative SMEs in Poland in the age of a deep transformation of the Polish economy. The authors try to verify the concept of B. A. Kirchoff about the relationship between innovation and enterprise growth. Some sector and market conditions of functioning of innovative SMEs are also analyzed in the paper. A study among 81 Polish SMEs from Lodz region confirms that there is an independence between enterprise innovation and its ability to create jobs. On one side, among analyzed enterprises about 14% was highly innovative fast growing. On the other side, low innovative and slowly growing made a high percentage. The research pointed an important factor of the ability of job creation - sector and market conditions, management problems (lack of experience, problems with gathering the initial capital) and poor public support. The shadow economy has a positive impact on growth rather than on innovation. However, it does not have a positive influence on expansion, innovation and new jobs creation undertaken simultaneously, which is the most desirable activities of the enterprise.